THE LOW ENERGY SPECTRUM OF COSMIC-RAY MESONS AT SEA LEVEL AT HIGH GEOMAGNETIC LATITUDES - Rose, D. C.; Voisin, A. G. (Canadian Journal of Physics, 1952)
The differential range spectrum of cosmic-ray mesons has been measured by three different methods the first of which was used at two northern geomagnetic latitudes 56.8 (Ottawa) and 83.0 (Resolute in the Canadian Arctic). In the first method the integral spectrum was measured by absorption, and after various corrections the differential spectrum was derived. In the second method the number of particles stopped in a block of lead was measured by a coincidence–anticoincidence arrangement of counters. In the third method the delayed coincidence method was used, the meson being identified by its decay electron. Over the range studied (ranges in lead up to 700 gm ∙ per cm ∙ 2 ) the results of the three methods are in general agreement and agree with others in that the smoothed data show only a small variation in intensity over the range studied. Some of the results suggest that a more detailed study of the spectrum might show some irregularities in the intensity variation with range. As would be expected no significant difference was found in the shape of the curves at the two stations.